Molecular characterization of the soxRS genes of Escherichia coli: two genes control a superoxide stress regulon. - Amábile-Cuevas, C F (1991)
The soxR locus of Escherichia coli K12 mediates transcriptional activation of a complex oxidative stress regulon in response to superoxide-generating (redox-cycling) agents. We have cloned the soxR locus, which is positioned near the uvrA gene at 92.2 min on the genetic map, by monitoring complementation of a delta soxR mutation. Subclones from the soxR region in the delta soxR strain simultaneously restored cellular resistance to the redox-cycling agent phenazine methosulfate and inducibility of at least two of the regulon proteins, glucose-6-phosphate dehydrogenase and endonuclease IV, by paraquat, another redox-cycling agent. DNA sequence analysis revealed the presence of two genes involved in activating the soxR regulon. These genes, named soxR and soxS, are arranged divergently with their 5' ends separated by only 85 bp. The predicted 12.9-kDa SoxS protein is related to the AraC family of one-component gene regulators, but corresponds only to the putative DNA-binding regions of these proteins. The 17.1-kDa SoxR protein bears significant homology only to the MerR family of proteins including a predicted DNA-binding helix-turn-helix and a cluster of cysteine residues positioned similarly to those that regulate the activity of MerR in response to Hg2+. This suggests that SoxR could be a metal-binding gene regulator that acts as the intracellular sensor for superoxide. SoxS is evidently the proximal activator of the regulon genes: antibiotic resistance and high-level expression of at least three of the regulon proteins was effected in vivo by the individual expression of SoxS, but not of SoxR, whether or not the cells were exposed to paraquat. These data, together with the recently reported paraquat-inducibility of the soxS gene (Wu, I., and Weiss, B. (1990) J. Bacteriol. 173, 2864-2871), indicate that SoxR and SoxS may constitute a novel type of two-component regulatory system in which the two proteins act sequentially to activate transcription of the various regulon genes in response to superoxide stress.